Closure - Management, Journal of Infrastructure & Facility Asset (Journal of Infrastructure & Facility Asset Management, 2023)
Journal of Infrastructure & Facility Asset ManagementVolume 5, Issue 1, April 2024                                       (e) ISSN 2656-8896  (P) ISSN 2656-890X JIFAM, Vol.5, Special Issue 1, February 2023The Dynamics of State-Owned Assets Insurance Regulation Drafting from Regulation Theory Lens       Fakhri Nurfaiz & Taufik Raharjo Alternative of Soil Improvement Methods on Organic Soil Using Preloading and Vertical Piles for Embankment with Varied Heights. Case Study: Construction of Batanjung Port Access Road in Pulang Pisau Regency, Central Kalimantan       Dedy Manudianto, Noor Endah & Hardy Pangihutan SiahaanJIFAM, Vol.4, Issue 2, August 2022Comparison of Embankment Reinforcement Requirements with Geotextile on Soft Soil with 2D and 3D Slope Stability Analysis Methods       Nur Arfiati Shoffiana, Yudhi Lastiasih & Trihanyndio Rendy Satrya Evaluation of Smart Mobility Indicators in Responding COVID-19 Pandemic in Indonesia       Shanty Y. Rachmat & Ganesha G. Mangkoesoebroto Geotechnical Mapping for Soil Physical and Mechanical Parameters and Hard Soil Depth in Badung Regency       Zefira Wisna Maulidha, Trihanyndio Rendy Satrya & Yudhi Lastiasih The Physical Integration of Smart Transportation Characteristics of Suroboyo Bus and the Feeder       Cindy Nur Aziza Rahman, Eko Budi Santoso & Siti Nurlaela The Adequacy of Public Bus Fleet During the Covid-19 Pandemic (Case of The Transjakarta Corridor 1 DKI Jakarta, Indonesia)       Amanda Dian W.Kusumawardani, Ibnu Syabri, Fika Novitasari & Naya C. Drestalita